2016
DOI: 10.1111/ejn.13354
|View full text |Cite
|
Sign up to set email alerts
|

Reducing falls in Parkinson's disease: interactions between donepezil and the 5‐HT6 receptor antagonist idalopirdine on falls in a rat model of impaired cognitive control of complex movements

Abstract: Falls are a leading cause of death in the elderly and, in a majority of patients with Parkinson's disease (PD), the leading levodopa-insensitive cause of hospitalization and long-term care. Falling in PD has been attributed to degeneration of forebrain cholinergic neurons that, in interaction with striatal dopamine losses, impairs the cognitive control of balance, gait, and movement. We previously established an animal model of these dual cholinergic-dopaminergic losses ("DL rats") and a behavioral test system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 66 publications
4
22
0
Order By: Relevance
“…Consistent with this possibility, the severity of cholinergic neuronal loss in the PPN correlates with the severity of parkinsonian symptoms in PD and lesions involving the PPN manifest with gait disturbances (Aziz et al, 1998; Rinne et al, 2008). We have recently demonstrated that the combination of idalopirdine and donepezil reduces falls in an animal model of PD with dual dopaminergic and cholinergic lesions (Kucinski et al, 2017). This, together with the activation of the PPT in the current study, would suggest that the combination treatment might have beneficial effects on gait and posture through activation of the brainstem cholinergic system.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this possibility, the severity of cholinergic neuronal loss in the PPN correlates with the severity of parkinsonian symptoms in PD and lesions involving the PPN manifest with gait disturbances (Aziz et al, 1998; Rinne et al, 2008). We have recently demonstrated that the combination of idalopirdine and donepezil reduces falls in an animal model of PD with dual dopaminergic and cholinergic lesions (Kucinski et al, 2017). This, together with the activation of the PPT in the current study, would suggest that the combination treatment might have beneficial effects on gait and posture through activation of the brainstem cholinergic system.…”
Section: Discussionmentioning
confidence: 99%
“…An animal model carrying a dual cholinergic‐dopaminergic loss (“DL rats”) was assessed for falls associated with traversing dynamic surfaces and distractors using a behavioral test system (Michigan Complex Motor Control Task) . These models are now used to test medical treatments …”
Section: Preventing Falls: Current Evidencementioning
confidence: 99%
“…For example, in a dual-lesion (cortical-cholinergic and striatal-dopaminergic) model of PD, the cholinergic lesion significantly affected rodents' vulnerability to distraction and falls only in combination with caudate dopaminergic lesions and vice versa -neither cholinergic nor dopaminergic lesions had much impact on these measures by themselves (Kucinski et al, 2013). Pharmacologic enhancement of cholinergic function (donepezil and idalopirdine) improved the ability to recover from distractor effects, especially the ability to re-instate correct performance after a short disruption (Kucinski et al, 2017). In contrast, large dopaminergic lesions (without a cholinergic lesion) led to low vigor for and control over movement, but without apparent effects on attention-motor interactions (Kucinski et al, 2015).…”
Section: Discussionmentioning
confidence: 98%